The History Of The Out-Of-School Educational Institutions’ of The Sport Orientation Work By Mass Media In The 50s-70s Of The Xx-Th Century - Nimych, Hanna (Pedagogical Discourse, 2013)
The article is devoted to the history of formation and disclosure activities of periodicals in the 50-ies and 70-ies of XX century. The titles of periodicals, the main topics of the publications are represented in the article. As the separate direction the author distinguishes articles, devoted to the coverage of the peculiarities of sport activityʼs organization in non-school educational institutions of the mentioned period. The analysis of normative documents relating to the organization of the main directions of the activities of periodicals is presented, as well as conditions for improving the work of the sports press and its main disadvantages. The role of pedagogical press sport in the popularization of physical culture and sports among the population of Ukraine is analyzed within the specified time period.